THE PHILOSOPHICAL ESSENCE OF ABU NASR FARABI'S RELIGIOUS AND MORAL OPPONENTS - Ruzmetova, Dilbar (Journal of Learning on History and Social Sciences, 2024)
In the article, we will dwell on the invaluable service of Abu Nasr Farabi in the development of science. The fact that Farobi put forward important philosophical and didactic ideas about man, created his original concept of education focusing on the best examples of Eastern culture, the scholar's views on human spiritual and moral qualities, human existence and its role in social life. the place, education and its main features, education - inculcation of ethnic qualities and arts based on knowledge to the people, its educational ideal, as well as the importance of philosophical and didactic views on man in youth education and its essence are analyzed.